An Investigation on Ontology Based Fuzzy Semantic Information Retrieval - Naren, J.; Rajeswari, D. Raja; Sannidhi, Nikhith; Vithya, G. (International Journal of Psychosocial Rehabilitation, 2024)
Information retrieval, a core research area, has caught the minds of many computer science researchers. The research survey is an amalgamation of various findings done in the effectiveness of ontology-based information retrieval with fuzzy logic content evaluation. The inference of the scan with many papers widens the understanding of a researcher on fuzzy ontology-based information retrieval, which has come by converting an ordinary ontology to a fuzzy ontology. The paper gives an explanatory note on several models used in information retrieval. Comprehensive comparative studies on algorithms in the areas revolving ontology with information retrieval are also prescribed. A framework on the existing OBIR (ontology-based information retrieval) being developed for education could be the next nearest work following the literature review, which remains the conclusion of the proposed work.